2001
DOI: 10.1021/jf000494j
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Antioxidative Peptides from Gelatin Hydrolysate of Alaska Pollack Skin

Abstract: Gelatin extracted from Alaska pollack skin was hydrolyzed with serial digestions in the order of Alcalase, Pronase E, and collagenase using a three-step recycling membrane reactor. The fraction from the second step, which was hydrolyzed with Pronase E, was composed of peptides ranging from 1.5 to 4.5 kDa and showed high antioxidative activity. Two different peptides showing strong antioxidative activity were isolated from the hydrolysate using consecutive chromatographic methods including gel filtration on a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
288
0
8

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(307 citation statements)
references
References 21 publications
11
288
0
8
Order By: Relevance
“…3 pH-shift process for production fish protein isolates (FPI) (adapted from Hultin et al 2005) are influenced by the degree of hydrolysis (Kristinsson and Rasco 2000). Proteins separated by partial enzyme hydrolysis are known to possess anti-oxidation properties against peroxidation of lipids and fatty acids (Kim et al 2001). …”
Section: Soluble Impurities Centrifuge Precipitationmentioning
confidence: 99%
“…3 pH-shift process for production fish protein isolates (FPI) (adapted from Hultin et al 2005) are influenced by the degree of hydrolysis (Kristinsson and Rasco 2000). Proteins separated by partial enzyme hydrolysis are known to possess anti-oxidation properties against peroxidation of lipids and fatty acids (Kim et al 2001). …”
Section: Soluble Impurities Centrifuge Precipitationmentioning
confidence: 99%
“…Although several studies have examined the fractionation and isolation of functional peptides from hydrolysates of fish skin (Kim et al, 2001a(Kim et al, , 2001bMendis et al, 2005), with the exception of Kim et al (2011), no research has evaluated the feasibility of using rockfish skin gelatin as a source of functional gelatin hydrolysates. The objective of this study was to obtain a fraction with high antioxidant activity from rockfish skin gelatin hydrolysates by fractionation through UF membranes.…”
Section: Radical Scavenging Activitymentioning
confidence: 99%
“…Mendis et al (2005) reported that antioxidant peptides isolated from hoki skin gelatin hydrolysate were composed of His-Gly-Pro-LeuGly-Pro-Leu. Kim et al (2001b) reported that the peptides (P1 and P2) fractionated and isolated from gelatin hydrolysate of Alaska pollock skin were composed of 13 and 16 amino acid residues, respectively, and that both peptides contained glycine residues at the C-terminus and repeating glycine-prolinehydroxyproline. These reports, as well as our results, suggest that sequential enzymatic hydrolysis of rockfish skin gelatin with Alcalase/Flavourzyme followed by fractionation are suitable methods for obtaining antioxidant peptides.…”
Section: Ace-inhibiting Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial enzymes, especially Alcalase 1 2.4L (from Bacillus licheniformis), have been repeatedly favored for fish hydrolysis due to the high degree of hydrolysis (DH) that can be achieved, compared to neutral or acidic enzymes, in a relatively short time under moderate conditions (Je, Park, & Kim, 2004;Kim, Kim, Byun, Joo, & Shahidi, 2001;Rajapakse, Mendis, Byun, & Kim, 2005;Shahidi & Amarowicz, 1996).…”
Section: Introductionmentioning
confidence: 99%